Valorisation of mine waste as carbon mineralisation feedstock - Gazzetti, EW; Bandstra, JZ; Diedrich, TR (Mine Closure 2023: 16th International Conference on Mine Closure, 2023)
Growing incentives to decarbonise the economy are creating new opportunities for valorising mine waste. One of these emerging opportunities involves carbon sequestration via carbon mineralisation using mine waste with amenable chemistry as mineral feedstock. At earth's surface, the process of converting atmospheric CO2 into stable mineral phases occurs naturally—and slowly—over geologic time scales. Mine waste presents a unique opportunity for enhanced carbon mineralisation due to large quantities of freshly exposed reactive surface area created by blasting, crushing, and other beneficiation processes. To date, most surficial carbon mineralisation demonstrations have targeted the mineral brucite, a mechanism that applies to less than 5% of mine waste types. Unlocking potential from the remaining 95% on human timescales requires site-by-site geochemical evaluations of waste material and subsequent development of waste management strategies designed to optimize carbon mineralisation. A geochemical modelling-based program has been developed and applied to rapidly assess the carbon mineralisation potential of a wide range of mine waste compositions. This program uses data routinely obtained through standard geochemical analyses. Modal mineralogy, bulk elemental compositions, and either site-specific (e.g., derived from bench-scale tests) or literature-based reaction rates are used to predict carbon mineralisation rates using a geochemical model operating in a batch-reactor configuration. The ability to opportunistically use data that many mines already have available allows for materials to be rapidly screened (and, if applicable, ranked) for carbon mineralisation potential prior to engaging in costly specialized programs. Initial applications of this model indicated that passive mineral carbonation rates—i.e., mineralisation occurring under routine conditions of mine waste management—at North American mine sites range up to approximately 0.44 kg CO2 per tonne of waste material per year. When scaled up to typical masses of mine waste management features, mineralisation can be appreciable. Furthermore, the geochemical model indicates that these rates can be improved substantially through mine waste management practices that are likely to enhance kinetics,including hydrological controls, grain size optimizations, and the introduction of heat. Outstanding themes requiringrefinement to advance state-of-the-art practices in carbon mineralisation include (i) scaling factors to improve suitability of literature-based kinetics in modelling efforts, (ii) changes to mineral reactivity with time, and (iii) verification/quantification methods at bench, pilot, and field scales.
Keywords: decarbonise; sequestration; mineralisation; carbonation; valorisation